Streptokinase or Alteplase for Acute Limb Ischemia? A Meta-Analysis - Agung Pradnyana Suwirya; Ni Nyoman Utami Wijayaswari Pande; Bagus Ari Pradnyana DS (HM Publisher, 2025)
Background: Acute limb ischemia (ALI) is a vascular emergency that necessitates prompt and effective treatment to restore blood flow and prevent limb loss. Thrombolytic therapy, particularly with agents like streptokinase and alteplase, plays a pivotal role in ALI management. This meta-analysis and systematic review aimed to compare the efficacy and safety of streptokinase and alteplase in treating ALI. Methods: A comprehensive search of PubMed, Embase, Science Direct, and the Cochrane Library databases was conducted up to August 13, 2024, to identify relevant studies. The inclusion criteria encompassed clinical trials involving patients diagnosed with ALI who received either streptokinase or alteplase as the initial thrombolytic treatment. The quality of the included studies was rigorously assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) and the Methodological Index for Non-Randomized Studies (MINOR) criteria. A meta-analysis was performed using the Mantel-Haenszel random-effects model to calculate risk ratios (RRs) with their corresponding 95% confidence intervals (CIs). Results: The final analysis included 20 studies, encompassing both qualitative and quantitative assessments. A comparative analysis of streptokinase and alteplase for limb salvage at 30 days revealed a significant advantage in favor of alteplase, with a relative risk ratio (RR) of 0.78 (95% CI 0.69-0.88, I² = 0%). Furthermore, streptokinase was associated with a higher rate of primary amputation, with an RR of 2.54 (95% CI 1.50-4.32, I² = 0%) compared to alteplase. The use of streptokinase also correlated with a higher risk of complications, including major bleeding (RR 1.75, 95% CI 0.04-84.30, I² = 77%) and minor bleeding (RR 1.41, 95% CI 0.60-3.32, I² = 0%). Conclusion: The findings of this meta-analysis underscore the superior efficacy of alteplase in achieving limb salvage in ALI, coupled with a more favorable safety profile. The preferential use of alteplase in clinical practice is recommended, particularly in patients with severe ischemia. However, careful patient selection and close monitoring are crucial when streptokinase therapy is considered.